An Enhancing Community Disaster Resilience in Tourism Villages: Insights from West Nusa Tenggara, Indonesia - Osmar Shalih; Heni Marta Diana Matita Putti; Falisha, Sania Indah Kirana Falisha (Universitas Negeri Semarang, 2025)
Historical records show that Lombok experienced significant damage from a tsunami triggered by geological activity in 1977. Kuta Village, located in southern Lombok, faces a high risk of earthquakes and tsunamis. This research aims to develop mitigation and preparedness recommendations for the area. Data was collected using a community preparedness survey in Kuta Village, observation with town watching, and focus group discussions. The results of the Household Preparedness Survey showed low scores in terms of knowledge, early warning, emergency response plans, and resource mobilization. Mitigation schemes in Kuta Village should prioritize improving both structural and non-structural aspects of the area. Structural measures should involve cooperation between local communities and the district government to maintain coastal vegetation. Non-structural approaches to mitigation include implementing tsunami mitigation measures into village development plans, improving community capacity, strengthening local government, and utilizing community-based early warning systems. To improve community capacity, the establishment of disaster-resilient tourism villages would be beneficial. In addition, promoting disaster-resilient families and raising tsunami awareness through locally sourced knowledge would also be useful.